Inclusion of Notary Positions on Social Media as a Form of Self-Promotion Based on The Notary Code of Ethics - Avicenna Galang Muhammad; Daly Erni (IHSA Institute, 2022)
The developments of technology make interaction between humans is easier, for example in the term of using social media. The Notary use is not prohibited, but the Notary should obey to the Notary Code of Ethics as a guide to Notary behaviours. The problems that will be discussed in this study are regarding the inclusion of a Notary position on social media and the procedure for imposing sanctions by the Notary Honorary Council against Notaries who violate the Notary Code of Ethics. In order to answer this problem, a normative juridical research method with a descriptive research typology is being used. The results of the analysis show that a Notary who lists his position on social media violates Article 4 paragraph (3) of the Notary Code of Ethics. This can be reviewed based on 2 (two) factors, namely aspects of forming personal branding and the Notary Code of Ethics. The Notary Honorary Council in carrying out its authority takes action based on reports both actively and passively. In giving the number of ethical sanctions, the Notary Honorary Council refers to the quantity and quality of the violations committed by the Notary. Based on this, Notaries are still allowed to use social media without including their position on social media. For the public, if they see someone who has listed the position of a Notary on social media, they can report it to the Notary Honorary Council. In addition, there is a need for a revision of the Notary Code of Ethics, especially regarding self-promotion because it does not follow the development of science and technology.